1994
DOI: 10.1128/iai.62.3.828-836.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a Candida albicans-binding proteoglycan secreted from rat submandibular salivary glands

Abstract: A previously identified Candida albicans-binding glycoprotein secreted from rat submandibular glands (RSMG) has been further purified from an aqueous RSMG extract by ion-exchange chromatography and gel filtration. Biochemical analysis of the glycoprotein revealed high levels of uronic acid and sulfate, suggesting that it was a proteoglycan. Its amino acid and carbohydrate compositions were similar to those observed for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
(57 reference statements)
0
7
0
1
Order By: Relevance
“…The reactive component of human saliva was identified as a low-molecular-weight mucin, MG2 in human saliva and rat submandibular gland (RSMG) mucin in rat saliva. The purified RSMG component had characteristics of both mucin and proteoglycan (200). The binding moiety contained glycosaminoglycans and human blood group A oligosaccharide, which are generally associated with proteoglycans and mucins, respectively.…”
Section: Binding Proteins (Receptors) For Host Ligandsmentioning
confidence: 99%
“…The reactive component of human saliva was identified as a low-molecular-weight mucin, MG2 in human saliva and rat submandibular gland (RSMG) mucin in rat saliva. The purified RSMG component had characteristics of both mucin and proteoglycan (200). The binding moiety contained glycosaminoglycans and human blood group A oligosaccharide, which are generally associated with proteoglycans and mucins, respectively.…”
Section: Binding Proteins (Receptors) For Host Ligandsmentioning
confidence: 99%
“…albicans adheres also to extracellular matrix proteins (7,8), possibly with the involvement of adhesins that mimic the complement receptors CR2 and CR3 (9). Moreover, it has been shown that C. albicans binds to salivary components, including mucins (10), proteoglycan (11), and proline-rich protein (12), suggesting that C. albicans has multiple mechanisms for adherence in the oral cavity. It is well known that C. albicans adhesion to mucosal and artificial surfaces in the mouth is enhanced by several factors such as germtube production, phospholipase, protease, other extracellular enzymatic activities, carbohydrates, pH and temperature (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…These adhesins may also assist in avoidance by C. albicans of host immune defenses (3,15). Recently it has been shown that C. albicans binds to salivary components, including mucins (12,17), proteoglycan (18), and fractions enriched in proline-rich proteins (4), suggesting that C. albicans has multiple mechanisms for adherence in the oral cavity.…”
mentioning
confidence: 99%